A Review on Automatic Speech Recognition System (International Journal of Engineering and Computer Science, 2015)
Speech is the most basic, common and efficient form of communication method for people to interact with each other. People are comfortable with speech therefore persons would also like to interact with computers via speech, rather than using primitive interfaces such as keyboards and pointing devices. At present, inputting the data in computer by speech and converting the data into the another form for eg. Text. with the help of automatic speech recognition system and its recognition by the computer is one of the developed scientific fields. As each language has its specific feature, the various speech recognition systems are investigated for the different languages. In this paper, we have classify the Automatic Speech Recognition System